CONCEPTS OF ISLAM AND ITS POLITICIZATION IN CENTRAL ASIA - Prof. Ilhomjon BEKMIRZAEV (Scholar Express Journal, 2022)
Islam has been fundamental to the life of Central Asia for more than a millennium. The Central Asian region has, in its turn, played an invaluable role in Islamic history. Many Muslim scholars, spiritual leaders, and dynasties originated from this region and contributed much to the development of Islamic sciences, culture, and civilization. The last three decades have been marked by the resurgence of Islam in post-Soviet Central Asia after the long seventy-year destruction and suppression of religious institutions, educational venues, and Islamic consciousness by the Soviet regime. Inasmuch as this religious resurgence is having a considerable impact on the personal and social lives of Central Asian Muslims, the issue of political Islam has become one of the most debated and controversial in political and academic circles, as well as in the expert community and in the media. Although it seems implausible to deny the threat of radical political Islam in Central Asia, we cannot ignore the fact that this threat can be employed and exacerbated by some power-holding groups to their own advantage. So, it is necessary to analyze political Islam and the Islamic resurgence in Central Asia in general in a more nuanced fashion. It seems often that “insurgent Islamism” or “creeping radicalism” have become catchall expressions for conventional threats and fears in Central Asia. Securityobsessed assessments turn out to be not only stereotyped, but also misleading, since they prevent us from understanding the region’s real problems
Keywords: Central Asia; Soviet regime; Central Asian Muslims; Uzbekistan